UPAYA PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN MELALUI PROGRAM BIMBINGAN ROHANI ISLAM PAGI PADA PERUSAHAN WINDA & RAFFI KOTA PADANG - Mistarija Mistarija (Universitas Islam Negeri Imam Bonjol Padang, 2020)
AbstractThe application of da'wah with the Islamic guidance approach in the realm of the industrial world is very much needed. Islamic guidance acts as a controller and conditioning of human psyche, so that it can stabilize its mental condition. Stable psychiatric conditions will enable humans to maximize their potential and carry out activities properly, including in the world of work. This paper will explain efforts to increase employee productivity through morning Islamic spiritual guidance programs at Winda & Raffi City companies. The Islamic spiritual guidance program has been able to spur the enthusiasm of employees to work optimally, thus encouraging the rapid development of the company.